Mexican Telecom Reform: private interest first? - Alvarez, Clara-Luz (UNAM, Instituto de Investigación Jurídicas, 2015)
Telecommunications reform, one of the pillars of President Enrique Peña Nieto’s highly-publicized structural reforms, was enacted to recognize as human rights access to: (i) information and communications technology; and (ii) broadcasting and telecommunications services, including broadband and the Internet. The reform also gave the Mexican government the authority to sanction or even split up companies engaged in monopolistic practices, and to establish ad hoc restrictions to minimize undue market advantages for dominant industry players – defined as companies that capture 50 percent market share measured by number of users/audience, capacity or network infrastructure. This article explores several aspects of this new legislation, including regulatory agencies; media and plurality; audience and users’ rights; restrictions to minimize market manipulation; mergers; data retention and geo-localization; and access for persons with disabilities. It also examines various aspects of the legislative process, as well as some broader implications of the new law.
Keywords: Telecommunications; Broadcasting; Audience; Mergers; Antitrust; Plurality; Competition; Telecomunicaciones; Radiodifusión; Audiencia; Concentraciones; Competencia económica; Pluralidad; Competencia